Altamira-PA: novos papéis de centralidade e reestruturação urbana a partir da instalação da UHE Belo Monte - José Queiroz de Miranda Neto; José Antônio Herrera (Confins)
In this article, we intend to analyse the new centrality role conferred to the city of Altamira since the arrival of Belo Monte’s hydropower plant. As a parameter for this analysis, we considered that Altamira is having a major role in the South East centrality of the Pará state, reaching up to nine urban centres between the Xingu River and the Transamazonica road (BR 230). The theoretical references used in this article are coupled with surveys about the city, urbanism in Brazil and in the Amazon area, with an emphasis on surveys linking urban restructuration and average sized cities. Official sources and field surveys indicate that Altamira is going through a transition in its shape and urban functions, altering its characteristics which amplifies its ability to articulate local urban centres. Belo Monte’s hydropower plant allowed, in this case, the induction of processes which resulted in the infrastructure’s expansion and the increase of goods and services supply, promoting a new sense in terms of urban centrality.